Proceedings. First Assembly of the Latin-America and Caribbean Seismological Commission - LACSC - Third Latin-American Congress of Seismol Third Latin-American Congress of Seismology (Earth Sciences Research Journal)
The Latin-American and Caribbean region is an area with a very complex tectonic setting, where stress and strain generated by the interaction of several lithospheric plates is being absorbed. Several regional fault systems, with moderate and high activity, represent a hazard for a significant part of the population (more than 500 million inhabitants). Given the recent developments in the mining and energy industries, a great deal of exploration has been focusing on this part of the world, and the potential extraction of mineral resources is going to generate important changes in vast areas of the American continent. Considering the geodynamic framework and the expectation of the extraction of economic resources, questions about the impact of human activities and the possible destabilizing of the relevant tectonic systems are raised. Many theoretical and applied geophysical studies have been developed in different regions of Latin-America and the Caribbean, mainly since the second half of the 20th century. There have been basically two motivations to carry out these studies: The evaluation of natural hazards and the exploration of economic resources. Such studies have mainly focused on the knowledge of: (a) the structure of the crust and upper mantle, (b) the regional tectonic evolution, (c) the local and regional seismic hazards, and (d) the geometry of geologic structures of economic interest. This part of the world has witnessed an excessive and disproportionate growth in the number of urban centers, evidenced by the increase in economic and social gaps. This situation puts a great portion of the population at a high level of vulnerability, which in addition to the natural hazard in the region, configures a scenario of high seismic risk. In this academic event, the relevant results associated with the seismotectonic behavior of this part of the world will be addressed, as well as the implications of active exploration of the tectonic conditions, the socio-economic impacts of exploration and extraction of economic resources, and the implementation of non-conventional techniques for exploring and mining that can contribute to sustainable development. We welcome contributions from around the world.